2020
DOI: 10.1007/s12264-020-00621-4
|View full text |Cite
|
Sign up to set email alerts
|

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice

Abstract: Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…After TN, the deletion of TLR4 did not reduce the expression of MyD88, a downstream molecule of TLRs [ 49 ]. A recent study on TN showed that TLR8 activate ERK and p38, and further increase the expression of pro-inflammatory cytokines in the trigeminal ganglion neurons [ 50 ]. In our study, MyD88, which is an adaptor for all TLRs (except TLR3).…”
Section: Discussionmentioning
confidence: 99%
“…After TN, the deletion of TLR4 did not reduce the expression of MyD88, a downstream molecule of TLRs [ 49 ]. A recent study on TN showed that TLR8 activate ERK and p38, and further increase the expression of pro-inflammatory cytokines in the trigeminal ganglion neurons [ 50 ]. In our study, MyD88, which is an adaptor for all TLRs (except TLR3).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs and Ca 2+ signaling interact with and regulate each other. TLRs (including TLR2, TLR3, TLR4, TLR7, TLR8 and TLR9) have been demonstrated to participate in cytokine production, activation of immunocytes, inflammation, and antiviral innate responses by regulating Ca 2+ signaling ( Tauseef et al, 2012 ; De Dios et al, 2020 ; Zhao et al, 2020 ). In particular, TLR4, which recognizes bacterial lipopolysaccharides (LPSs), is widely reported to alter cytoplasmic Ca 2+ levels and activates Ca 2+ signaling by regulating various Ca 2+ channels.…”
Section: Ca 2+ Signaling In Innate Immune and Anti...mentioning
confidence: 99%
“…For the study of TN, a variety of animal models (Table 1) [3,[40][41][42][43][44][45][46][47][48][49][50][51][52][53] have been developed. All of these animal models contributed to the discovery of vital information about the TN pathway or TN therapeutic management.…”
Section: Different Animal Models For Trigeminal Neuralgia Studymentioning
confidence: 99%